PENGEMBANGAN BIBIT UNGGUL PORANG (Amarphopallus oncophilus) MELALUI TEKNIK KULTUR IN VITRO UNTUK MENDUKUNG KETAHANAN PANGAN NASIONAL - Suheriyanto, Dwi; Romaidi, Romaidi; Resmisari, Ruri Siti (El-Hayah : Jurnal Biologi, 2012)
Porang (Amarphophallus. oncophyllus) is a type of plant tubers that have the potential and prospects for development in Indonesia. In addition to readily available, plants are also capable of producing carbohydrates and high harvest index. The last few years a very large porang needs. Porang plant propagation is vegetative and generative in which to make the seeds are ready to harvest takes between 4-6 months. This study aims to determine kinds of the appropriate medium for growing plants porang network and determine the concentration  of  each  medium,  so  we  get  a  superior  porang  plants.  Research  using factorial completely randomized design. The first factor is a growth regulator BAP concentration: 0 mg / l, 0.5 mg / l, 1.0 mg / l, 1.5 mg / l and 2.0 mg / l, while the second factor is the concentration of IBA 0 mg / l, 0.5 mg / l and 1.0 mg / l, in order to obtain 15 treatments and each treatment made 15 replications. Data were collected for the pengkalusan, contamination callus, callus mortality rate, number of buds, leaf buds height, number of leaves and root. The results showed that the addition of plant growth regulators (hormones) BAP in MS medium effect on the number of shoots, buds and the high number of young leaves. The addition of hormone IBA in MS medium pengkalusan affect the process and the number of roots. The addition of hormone BAP and IBA on MS medium did not significantly affect mortality contamination callus and callus. The interaction between BAP and IBA hormone given on MS medium did not significantly affect the pengkalusan, contamination callus, callus mortality rate, number of buds, leaf buds height, number of leaves and root